2023
DOI: 10.3390/jof9020146
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Main Pathogens Causing Postharvest Disease in Fresh Codonopsis pilosula during Different Storage Stages and Ozone Control against Disease and Mycotoxin Accumulation

Abstract: Codonopsis pilosula is an important Chinese herbal medicine. However, fresh C. pilosula is prone to decay during storage due to microorganism infections, seriously affecting the medicinal value and even causing mycotoxin accumulation. Therefore, it is necessary to study the pathogens present and develop efficient control strategies to mitigate their detrimental effects on the herbs during storage. In this study, fresh C. pilosula was collected from Min County in Gansu Province, China. The natural disease sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our previous studies suggested that P. expansum is the main pathogen causing fresh C. pilosula blue mold during the postharvest storage period, which seriously impairs the quality of the fresh C. pilosula after harvest [ 19 ]. In this study, it was found that 2 mg L −1 ozone fumigation treatment significantly reduced the disease incidence of the blue mold of C. pilosula , inhibited the development of the blue mold of C. pilosula , reduced the accumulation of patulin, and alleviated the weight loss of C. pilosula to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies suggested that P. expansum is the main pathogen causing fresh C. pilosula blue mold during the postharvest storage period, which seriously impairs the quality of the fresh C. pilosula after harvest [ 19 ]. In this study, it was found that 2 mg L −1 ozone fumigation treatment significantly reduced the disease incidence of the blue mold of C. pilosula , inhibited the development of the blue mold of C. pilosula , reduced the accumulation of patulin, and alleviated the weight loss of C. pilosula to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were collected every 7 days for patulin analysis. Patulin accumulation was determined based on the method by Lv [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…A. elegans was previously isolated and purified from tissues affected by C. pilosula mucor rot disease in the laboratory. The identification was carried out through morphological and molecular biological methods [14]. The isolated A. elegans was stored at 4 • C on PDA (potato dextrose agar) culture medium for future use.…”
Section: Methodsmentioning
confidence: 99%
“…Field experiments were carried out from April 2022 to November 2022 at Kaishengyuan Agricultural Professional Cooperative, Minxian County, Dingxi City, Gansu Province, China (103 • 48 ′ 25 ′′ E, 34 • 29 ′ 20 ′′ N, elevation 2603.15 m). The research site is located in the transition zone from a temperate semi-humid climate to an alpine humid climate, with an average annual temperature of 5.5 • C. The annual precipitation is 635 mm, the annual precipitation is 635 mm, and the average sunshine duration is 2214.9 h. The soil type is black soil with a pH of 7.97, alkaline-dissolved nitrogen of 94.52 mg•kg −1 , 21.80 mg•kg −1 quick phosphorus, 41.11 mg•kg −1 quick potassium, and 24.11 g•kg −1 organic matter [13].…”
Section: Research Sitementioning
confidence: 99%